2023
DOI: 10.1002/jbio.202200284
|View full text |Cite
|
Sign up to set email alerts
|

Wide‐field Stokes polarimetric microscopy for second harmonic generation imaging

Abstract: We employ wide-field second harmonic generation (SHG) microscopy together with nonlinear Stokes polarimetry for quick ultrastructural investigation of large sample areas (700 μm  700 μm) in thin histology sections. The Stokes vector components for SHG are obtained from the polarimetric measurements with incident and outgoing linear and circular polarization states. The Stokes components are used to construct the images of polarimetric parameters and deduce the maps of ultrastructural parameters of achiral and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…CD-SHG utilizes the normalized difference in SHG intensity between right- and left-handed circularly polarized excitation and gives a parameter related to the out of plane angle of collagen fibrils. It has been commonly assumed that the sign of CD-SHG indicates the relative out of plane polarity of a fibril [ 9 , 10 , 12 15 ] as this is the expected result if the SHG emitter adheres to the electric dipole approximation [ 9 , 10 ]. However, recent results have shown that the sign of CD-SHG is invariant upon flipping the out of plane orientation of the sample for collagen in human cornea, murine fascia, and collagen fibrils assembled in-vitro [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD-SHG utilizes the normalized difference in SHG intensity between right- and left-handed circularly polarized excitation and gives a parameter related to the out of plane angle of collagen fibrils. It has been commonly assumed that the sign of CD-SHG indicates the relative out of plane polarity of a fibril [ 9 , 10 , 12 15 ] as this is the expected result if the SHG emitter adheres to the electric dipole approximation [ 9 , 10 ]. However, recent results have shown that the sign of CD-SHG is invariant upon flipping the out of plane orientation of the sample for collagen in human cornea, murine fascia, and collagen fibrils assembled in-vitro [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that CD-SHG may be a product of additional contributions to SHG in collagen fibrils beyond the electric dipole approximation, such as magnetic dipole effects. However, these results have recently been contradicted, with CD-SHG being observed to change sign as relative fibril orientation changes along a rat tail tendon [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…its sign is different between two sides of the same buckle) as expected based on equation (2b). The CD values are found to be almost always positive near the center of the fibril, where we know polarity changes are occurring, indicating that CDSHG reveals out of plane fibrils, but not their relative polarity, in agreement with [5] and contradicting [7,12]. Some regions near the edge of the fibril are found to have negative CD values which we attribute to an edge effect resulting from the nonuniform focal field as is the case for ρ.…”
Section: Effect Of Out Of Plane Orientation On Pshg Measurementsmentioning
confidence: 70%
“…It has long been presumed that the sign of CDSHG from collagen (i.e. preference for right-handed vs left-handed excitation) reveals the relative out of plane polarity of collagen fibrils [6][7][8][9][10][11]. However recent attempts to test this hypothesis on collagen in tissue have yielded contradictory results [5,7,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation